1999
DOI: 10.1046/j.1463-1318.1999.00044.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of faecal incontinence: obstetric and constipation‐related risk factors; a population‐based study

Abstract: A higher prevalence of faecal incontinence than previously reported was observed, particularly in males. The prevalence of urinary incontinence was consistent with other studies. Faecal and urinary incontinence are important community health problems in both sexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 23 publications
0
69
0
Order By: Relevance
“…This could be because men seem to be more reluctant to consult about this condition, as mentioned earlier. 4,8 Our study clearly shows that clinical severity alone is just one aspect of fecal incontinence. Even if severity is moderate or mild, fecal incontinence is very likely to affect QoL, with women appearing to be particularly negatively affected.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…This could be because men seem to be more reluctant to consult about this condition, as mentioned earlier. 4,8 Our study clearly shows that clinical severity alone is just one aspect of fecal incontinence. Even if severity is moderate or mild, fecal incontinence is very likely to affect QoL, with women appearing to be particularly negatively affected.…”
Section: Discussionmentioning
confidence: 62%
“…Although prevalence in women is thought to be higher than in men, 4 usually as a consequence of childbirth-related injuries, [12][13][14] some studies have failed to find clear epidemiological differences between the sexes, whereas other studies have actually reported higher prevalence rates for men than for women. 8 In a systematic review, Chiarelli et al 15 found very similar prevalence rates for both sexes. Moreover, it has been suggested that prevalence data may be distorted by men being more unwilling to report fecal incontinence than women.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Each 5-unit increase in BMI increases the risk of UI by 60% [50,51]. Co-morbidities, type 2 diabetes [52,53], cough in chronic obstructive pulmonary disease (COPD), frequent urinary tract infections [35], history of arthritis and chronic constipation [53][54][55][56][57] are known to increase the risk of developing UI. Women suffering from type 2 diabetes for at least a year or more are prone to develop UI [52,58].…”
Section: Risk Factors Associated With Urinary Incontinencementioning
confidence: 99%